Penerapan Akuntabilitas dan Transparansi dalam Pengelolaan APBdesa: Studi di Desa Sintuwulemba Kabupaten Poso - Feliks Arfid Guampe; Jeff Maurits Mokodompit; Fredrik Bastian Kawani; Olvit Olniwati Kayupa; Rizka Firstiani (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to find out how the implementation of accountability and transparency in the management of the Village Budget (APBDesa) in Sintuwulemba Village, Poso Regency, Central Sulawesi Province, is carried out. The researcher used a qualitative approach with in-depth interviews as the research method. Data were obtained by conducting interviews with three key informants consisting of the village secretary, the village treasurer, and the Village Consultative Body. The research findings indicate that the Sintuwulemba village government has applied the principle of accountability in the management of village funds. This is evident from the planning, implementation, administration, and accountability processes that are open, involving the community in every process. In terms of transparency, the Sintuwulemba village government has applied the principle of transparency where every village development policy and the use of village finances always go through the village deliberation stage. These two principals have made Sintuwulemba Village one of the successful villages in implementing village development and good village fund management in Poso Regency. These steps are also those that need to be emulated by other villages in Poso Regency and its surroundings.